2022
DOI: 10.1093/eurjcn/zvac061
|View full text |Cite
|
Sign up to set email alerts
|

Patient motivation and adherence to an on-demand app-based heart rate and rhythm monitoring for atrial fibrillation management: data from the TeleCheck-AF project

Abstract: Aims The aim of this TeleCheck-AF sub-analysis was to evaluate motivation and adherence to on-demand heart rate/rhythm monitoring app in patients with atrial fibrillation (AF). Methods and results Patients were instructed to perform 60 s app-based heart rate/rhythm recordings 3 times daily and in case of symptoms for 7 consecutive days prior to teleconsultation. Motivation was defined as number of days in which the expected n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 25 publications
0
4
1
Order By: Relevance
“…Of note, the total inclusion rate of 31% in this single centre study was relatively low in our series of consecutive patients and younger patients were more willing to participate in the study. These two observations differ from the overall results of the complete TeleCheck-AF analysis ( 23 ). This may be attributed to the pragmatic onboarding approach or clinical scenario specific factors including general scepticism towards the technology, the timepoint of inclusion during the long preparatory outpatient visit prior to ablation, or limited digital literacy.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Of note, the total inclusion rate of 31% in this single centre study was relatively low in our series of consecutive patients and younger patients were more willing to participate in the study. These two observations differ from the overall results of the complete TeleCheck-AF analysis ( 23 ). This may be attributed to the pragmatic onboarding approach or clinical scenario specific factors including general scepticism towards the technology, the timepoint of inclusion during the long preparatory outpatient visit prior to ablation, or limited digital literacy.…”
Section: Discussioncontrasting
confidence: 94%
“…This may be attributed to the pragmatic onboarding approach or clinical scenario specific factors including general scepticism towards the technology, the timepoint of inclusion during the long preparatory outpatient visit prior to ablation, or limited digital literacy. Additionally, motivation and adherence to perform the recommended number of measurements was lower than in the total TeleCheck-AF cohort ( 23 ). However, the higher motivation and adherence in those patients who recorded arrhythmias might reflect the importance of the symptom-driven recordings in this specific clinical scenario post PVI.…”
Section: Discussionmentioning
confidence: 83%
“…Our population’s mean age was younger; therefore, the trend of compliance increasing with age is in agreement with previous studies. A subanalysis of the TeleCheck-AF study showed that compliance increased with age [ 27 ]. In general, this tendency can be explained by several factors.…”
Section: Discussionmentioning
confidence: 99%
“…Data indicate a positive center and patient experience. 50 The effect of this intervention on clinical outcomes will be investigated in a RCT. A structured follow-up packages guiding the rehabilitation at home have been updated for mAFA (mAFA III) and are suitable for patients receiving drug treatment only or left atrial appendage occluder.…”
Section: Atrial Fibrillation Management Supported By Digital Devicesmentioning
confidence: 99%